2002
DOI: 10.1163/15685680260433913
|View full text |Cite
|
Sign up to set email alerts
|

Shading and texture: separate information channels with a common adaptation mechanism?

Abstract: We outline a scheme for the way in which early vision may handle information about shading (luminance modulation, LM) and texture (contrast modulation, CM). Previous work on the detection of gratings has found no sub-threshold summation, and no cross-adaptation, between LM and CM patterns. This strongly implied separate channels for the detection of LM and CM structure. However, we now report experiments in which adapting to LM (or CM) gratings creates tilt aftereffects of similar magnitude on both LM and CM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 26 publications
4
35
3
Order By: Relevance
“…Lu & Sperling, 1995;Scott-Samuel & Georgeson, 1999;Wilson, Ferrera, & Yo, 1992). Our studies of first-and second-order grating detection, and perceptual aftereffects, revealed a similar picture of separate encoding pathways responding to the spatial structure of luminance modulation (LM) and contrast modulation (CM) (Georgeson & Schofield, 2002;Schofield & Georgeson, 1999). In this paper we focus specifically on contrast modulation (CM) as a second-order property (see Fig.…”
Section: Introductionmentioning
confidence: 82%
“…Lu & Sperling, 1995;Scott-Samuel & Georgeson, 1999;Wilson, Ferrera, & Yo, 1992). Our studies of first-and second-order grating detection, and perceptual aftereffects, revealed a similar picture of separate encoding pathways responding to the spatial structure of luminance modulation (LM) and contrast modulation (CM) (Georgeson & Schofield, 2002;Schofield & Georgeson, 1999). In this paper we focus specifically on contrast modulation (CM) as a second-order property (see Fig.…”
Section: Introductionmentioning
confidence: 82%
“…One plausible explanation for such a finding (in the context of the above research) would be that the discrimination task probes a later processing stage, where first-and second-order pathways have been re-integrated. This idea is further supported by a cross-over of the tilt after-effect between first-and second-order cues (Georgeson and Schofield, 2002), and the finding that the tilt illusion transfers between first-and second-order cues (Dakin et al, 1999;.…”
Section: Independence Of First and Second-order Visionmentioning
confidence: 76%
“…The cross-over of after-effects between cues has been taken to indicate the integrated detection of those cues. However, in the light of apparently conflicting detection and adaptation results (such as those of Georgeson and Schofield, 2002) it seems likely that aftereffects are more indicative of cue integration after detection has taken place, rather than at the detection stage.…”
Section: Adaptationmentioning
confidence: 97%
See 1 more Smart Citation
“…The present findings of phase-dependent combination are not incompatible with either of these schemes. Models based on human psychophysics have involved separate early detection of the two kinds of stimuli, with subsequent interactions at a later stage (Georgeson and Schofield, 2002) As a baseline reference, it is worth considering that a cortical neuron might just linearly add the separately computed responses to LM and CM stimuli. In the case of a simple-type cell, the modulated responses to the LM and CM stimuli would sum maximally at one phase and cancel out at the opposite phase, giving a PDI approaching unity.…”
Section: Neural Mechanismsmentioning
confidence: 99%